2023
DOI: 10.3390/horticulturae9010106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Melatonin on Chrysanthemum Physiological Characteristics and Photosynthesis under Drought Stress

Abstract: Melatonin has been confirmed to relieve drought stress in various plant species. However, the mechanism in garden chrysanthemums remains to be elucidated. Here, we examined the putative role of exogenous melatonin application in improving drought-stress tolerance in Chrysanthemum seedlings. Treatment with melatonin (100 µM) significantly mitigated the negative effects of drought stress on the seedling photosynthetic parameters and physiological and biochemical indexes. The increased tolerance conferred by exog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…As a result, melatonin-sprayed plants showed an increase in F v /F m , relative water content, and chlorophyll content compared with plants without melatonin spray. Similar findings have been reported in studies conducted on chrysanthemum ( Luo et al., 2023 ) and strawberry ( Manafi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…As a result, melatonin-sprayed plants showed an increase in F v /F m , relative water content, and chlorophyll content compared with plants without melatonin spray. Similar findings have been reported in studies conducted on chrysanthemum ( Luo et al., 2023 ) and strawberry ( Manafi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Luteolin and its derivatives exhibit exceptional properties in scavenging ROS and protecting cells during water deficit stress [ 44 ]. This experiment combined with previous studies suggested that melatonin may enhance the antioxidant capacity of plants by regulating DEGs in the phenylpropanoid and flavonoid synthesis pathways [ 39 , 43 , 45 , 46 , 47 ]. However, these results need to be further confirmed by rigorous field trials.…”
Section: Resultssupporting
confidence: 62%
“…Melatonin treatment through foliar and root irrigation in soybean resulted in a slight increase in chlorophyll levels and a reduction in ABA content compared with control plants, indicating improved drought resistance [ 72 ]. Furthermore, in Chrysanthemum seedlings, exogenous application lessened the impact of drought stress on the photosynthetic mechanism, promoted seedling growth, reduced water loss, preserved chlorophyll levels, increased soluble protein and sugar levels, and enhanced antioxidant enzyme activity, leading to improved drought tolerance [ 73 ]. Finally, foliar treatment on Moringa oleifera enhanced photosynthetic pigment constituents, and the accumulation of IAA and phenolics, resulting in increased photosynthesis [ 74 ].…”
Section: Melatonin and Its Protective Effects On Photosynthetic Machi...mentioning
confidence: 99%